The Influence of Digital Marketing, Product Quality, and Store Atmosphere on Purchase Decisions at McDonald’s in Surabaya (A Study on Students of the Faculty of Economics and Business, University of 17 August 1945 Surabaya) - Bryan Nafiri Widodo; Endah Budiarti (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
in fulfilling most human needs. These developments have had a significant impact on the marketing industry. Therefore, entrepreneurs must identify suitable promotional strategies for their companies with the aim of using technological advancements to increase purchasing decisions. For example, this can be done by means of Digital Marketing, Product Quality and Store Atmosphere.This study was conducted to determine and analyze whether Digital Marketing, Product Quality and Store Atmosphere have a positive and significant effect on McDonald’s Purchasing Decisions both simultaneously and partially. The sample in this study were students of the Faculty of Economics and Business, University of August 17, 1945 Surabaya. The sample of this study amounted to 100 respondents. The technique used in this research is the Non-Probability Sampling Technique which is a non randomly selected sampling technique using the Quota Sampling type with the Lemeshow formula. Data collection through distributing questionnaires online, namely through G-Form. The data analysis method uses multiple regression analysis with SPSS version 26 software for data processing.Through this research, it can be known and analyzed that Digital Marketing has a Positive and Significant Effect on McDonald’s Purchasing Decisions. Research can also be known and analyzed that Product Quality has a Positive and Significant Effect on McDonald’s Purchasing Decisions. In addition, research can also be known and analyzed that Store Atmosphere has a Positive and Significant Effect on McDonald’s Purchasing Decisions.